ESTIMATING MAIZE EAR GRAIN YIELDS ON FARM - Elsahookie, M. M.; Cheyed, S. H.; Dawood, A. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Crop growth modelling is one of the important sciences in field crop sciences for it helps to reduce time and effort in searching for a fact or result. This article was dealed with a formula to predict maize ear grain weight when plants still standing on farm. Two genotypes of maize were used in this trial, a hybrid of feed maize was used in 2018 and an open-pollinated cultivar of pop corn in 2019. Ear length and diameter were measured on 50 randomly taken plants of full seed – set before harvest .Ears were harvested later, air dried ,threshed and weighed, then yield adjusted to 15% moisture .Ears were considered as cylinder ,and volumes of each ear were calculated .Date of observed ear grain weights and their volumes were analyzed for their correlation and regression ,they were fit in both years .The expected ear grain weight in 2018 formula was: expected dry ear grain weight (g) = - 0.1342 + 0.4871 ear volume (cm3) and in 2019 , the formula was : expected dry ear grain weight(g) = +0.3509 + 0.4776 ear volume (cm3). Date of observed and expected dry ear grain weights was analyzed by t- test. The results showed high similarity between observed and expected ear weights, indicating that these two equations will be helpful to estimate dry ear grain weight of maize, while plants still on farm.